Faktor yang Berhubungan dengan Kejadian Dbd pada Anak di Wilayah Kerja Puskesmas Oesapa Kota Kupang - Melda Rosanti Babys; Afrona Takaeb; Soleman Landi (Yayasan Literasi Sains Indonesia, 2024)
Dengue Hemorrhagic Fever (DHF) is still a health problem in the Oesapa Community Health Center working area. Data of dengue fever sufferers at the Oesapa Community Health Center for the last 3 years from 2020 there were 279 cases, in 2021 there were 94 cases and in 2022 there were 60 cases. This research aims the relationship between preventive measures, level of education, and support from families and health workers with the incidence of Dengue Hemorrhagic Fever in children in the working area of ​​the Oesapa Community Health Center, Kupang City. The type of research used is quantitative, analytical observational in nature. This research uses a case control or case control survey design. The sample in this study amounted to 94 respondents. The sampling technique used was simple random sampling with matching. Data analysis used with the Chi square test with a confidence level of 95% (α = 0.05). The results of the study showed that the factors related to the incidence of dengue fever were the action factor p= 0.007 (OR= 3.419), the education factor p= 0.023 (OR= 2.843), the family support factor p= 0.000, while the factors that were not related to the incidence of dengue fever were factors support from health workers p= 0.208. Lack of understanding of dengue prevention and control efforts is one of the factors in the occurrence of dengue fever so it is highly hoped that the participation of all family members in prevention efforts with the 3 M Plus movement.